Reform, foreign technology, and leadership in the Russian Imperial and Soviet navies, 1881–1941 - Demchak, Tony Eugene (Kansas State University, 2016)
This dissertation examines the shifting patterns of naval reform and the implementation of foreign technology in the Russian Empire and Soviet Union from Alexander III’s ascension to the Imperial throne in 1881 up to the outset of Operation Barbarossa in 1941. During this period, neither the Russian Imperial Fleet nor the Red Navy had a coherent, overall strategic plan. Instead, the expansion and modernization of the fleet was left largely to the whims of the ruler or his chosen representative. The Russian Imperial period, prior to the Russo-Japanese War, was characterized by the overbearing influence of General Admiral Grand Duke Alexei Alexandrovich, who haphazardly directed acquisition efforts and systematically opposed efforts to deal with the potential threat that Japan posed. The Russo-Japanese War and subsequent downfall of the Grand Duke forced Emperor Nicholas II to assert his own opinions, which vacillated between a coastal defense navy and a powerful battleship-centered navy superior to the one at the bottom of the Pacific Ocean. In the Soviet era, the dominant trend was benign neglect, as the Red Navy enjoyed relative autonomy for most of the 1920s, even as the Kronstadt Rebellion of 1921 ended the Red Navy’s independence from the Red Army. M. V. Frunze, the People’s Commissar of the Army of Navy for eighteen months in 1925 and 1926, shifted the navy from the vaguely Mahanian theoretical traditions of the past to a modern, proletarian vision of a navy devoted to joint actions with the army and a fleet composed mainly of submarines and light surface vessels. As in the Imperial period, these were general guidelines rather than an all-encompassing policy. The pattern of benign neglect was shattered only in 1935, when Stalin unilaterally imposed his own designs for a mighty offensive fleet on the Soviet military, a plan that was only interrupted by the outbreak of World War II.
Keywords: Russian Empire; Soviet Union; Naval history; Foreign technology transfer; Nicholas II; Joseph Stalin